2009
DOI: 10.1007/s10517-009-0536-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Proliferative Characteristics of Vero and MDCK Cells during Culturing in Nutrient Media on the Basis of Hydrolysates of Plant Proteins

Abstract: Morphological and proliferative characteristics of cultured Vero and MDCK cells were compared after growth in nutrient media of the basis of enzymatic hydrolysates of rice flour proteins and soybean flour proteins or control media (DMEM and Axcevir-MDCK). These media had a strong stimulatory effect on the growth of cultured Vero cells (addition of 3% fetal bovine serum, Gibco), but did not modulate the morphology of this culture. Culturing of MDCK cells in nutrient media on the basis of enzymatic hydrolysates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Current protocols developed to obtain new potential drugs consider evaluating the possible cytotoxic effect that the synthesized compounds could generate in cell models, both healthy and related to the pathology which are intended to treat; thus, herein we conducted cell‐based assays measured as the potential decrease in the cell viability through the blue trypan dye [49,50] . MDCK cells employed (Figure 9A–D) as a cell lines suitable as transfection host and useful for influenza research, [51–52] were not able to respond even to the maximum concentrations assayed as is possible to notice in the cell cultures observed at 40X and 100X (Figure 9C and 9D), in which is not possible to observe the presence of apoptotic bodies or any membrane damage caused for the compound, a hint of the non‐toxicity of 5 , additional, for this cell model was not able to determine a CC 50 even to a concentration upper to 500 μM and until 1 M. Another important issue referent to the non‐toxicity of the assayed compound was yielded by Vero cell lines (Figure 10A–D), used as host cells for growing viruses, such behavior is very similar to the findings obtained in MDCK cells, indeed, 5 is not able to produce some damage at the cell membrane at the 500 μM concentration assayed, but it is clearly evident that the 1 M concentration modified some features of the cell membrane visible as a spherulated cell shape, not proper to the cell lineage which Vero cells show, [53,54] but without formation of apoptotic bodies, as is observed in Figure 10D, this result yielded by trypan blue vital dye, establishes an optimal range for the subsequent assayed concentrations for below of 1 M in order to evaluate the antiviral activity. Lastly, the analysis of the probable cytotoxic effect mediated once the compound was absorbed and subsequent pumped‐out of the cell by transporters as MDR1 (also called P‐glycoprotein or ABCB1) was carried out employing the HeLa cell lines (Figure 11A–D) as model of multiple drug resistance (e. g., in chemotherapy resistance) [55–57] yield encouraging results which completes a profile of security about the non‐toxicity of 5 , such results are appreciable in the Figure 11 which shown that the assayed compound was not able no induce any change in the cell morphology even at maximum concentrations assayed, interestingly, this result correlates with the probable concentration‐dependent behavior of the assay, in which was visible the formation of black denser clumps precipitated at the maximum concentrations assayed (500 μM and 1 M), such finding correlates with the role of proteins as MDR1 responsible of pump‐out drug from the cell inner to surrounding media overexpressed in HeLa cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Current protocols developed to obtain new potential drugs consider evaluating the possible cytotoxic effect that the synthesized compounds could generate in cell models, both healthy and related to the pathology which are intended to treat; thus, herein we conducted cell‐based assays measured as the potential decrease in the cell viability through the blue trypan dye [49,50] . MDCK cells employed (Figure 9A–D) as a cell lines suitable as transfection host and useful for influenza research, [51–52] were not able to respond even to the maximum concentrations assayed as is possible to notice in the cell cultures observed at 40X and 100X (Figure 9C and 9D), in which is not possible to observe the presence of apoptotic bodies or any membrane damage caused for the compound, a hint of the non‐toxicity of 5 , additional, for this cell model was not able to determine a CC 50 even to a concentration upper to 500 μM and until 1 M. Another important issue referent to the non‐toxicity of the assayed compound was yielded by Vero cell lines (Figure 10A–D), used as host cells for growing viruses, such behavior is very similar to the findings obtained in MDCK cells, indeed, 5 is not able to produce some damage at the cell membrane at the 500 μM concentration assayed, but it is clearly evident that the 1 M concentration modified some features of the cell membrane visible as a spherulated cell shape, not proper to the cell lineage which Vero cells show, [53,54] but without formation of apoptotic bodies, as is observed in Figure 10D, this result yielded by trypan blue vital dye, establishes an optimal range for the subsequent assayed concentrations for below of 1 M in order to evaluate the antiviral activity. Lastly, the analysis of the probable cytotoxic effect mediated once the compound was absorbed and subsequent pumped‐out of the cell by transporters as MDR1 (also called P‐glycoprotein or ABCB1) was carried out employing the HeLa cell lines (Figure 11A–D) as model of multiple drug resistance (e. g., in chemotherapy resistance) [55–57] yield encouraging results which completes a profile of security about the non‐toxicity of 5 , such results are appreciable in the Figure 11 which shown that the assayed compound was not able no induce any change in the cell morphology even at maximum concentrations assayed, interestingly, this result correlates with the probable concentration‐dependent behavior of the assay, in which was visible the formation of black denser clumps precipitated at the maximum concentrations assayed (500 μM and 1 M), such finding correlates with the role of proteins as MDR1 responsible of pump‐out drug from the cell inner to surrounding media overexpressed in HeLa cancer cells.…”
Section: Resultsmentioning
confidence: 99%